Aktivitas Antioksidan Granul Instan Ekstrak Bunga Telang (Clitoria ternatea L) Sebagai Antidiabetes: Antioxidant Activity Of Instant Granules Of Telang Flower Extract (Clitoria ternatea L) As Antidiabetes - Fani Temarwut, Farid; Arif, Mutmaina; Rahmatia (Jurusan Farmasi Poltekkes kemenkes Makassar, 2025)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action, or both. DM can be classified into several types, namely, type 1 DM, type 2 DM, existing type DM. Type 2 DM is one of the most common types, which is more than 90-95%. The purpose of this study was to formulate instant granules of Telang Flower extract (Clitoria ternatea L) and determine antioxidant activity and antidiabetic activity. This research is a laboratory experiment involving instant granule formulations that are tested for physical characteristics, then tested for antioxidant activity using DPPH and Pretest-Postest Control Group Design antidiabetic activity test on White Rats. The results of observations of instant granule characteristics testing which include organoleptical tests, flow speed, angle of repose, moisture content, dissolving time and pH meet the granule requirements. the results of the antioxidant activity test IC50 value F1 155.39, F2 115.73, F4 143.93 and F5 148.25 where the four formulas show moderate antioxidant characteristics, while the IC50 nlai F5 262.86 is included in the weak antioxidant category. The measurement of blood glucose levels before alloxan induction (pree) and after alloxan induction (mid) increased where in FI 9. 63>267.33 mg/dL, F2 105.66>248.00, mg/dL F3 99.00>217.66 mg/dL F4 99.00>263.33 mg/dL and F5 104.00>247.33 mg/dL, while in healthy control (without treatment) no increase occurred 97.66 mg/dL, while the decrease in glucose levels after alloxan induction (mid) and after being given instant granule preparations (post) on the 11th day decreased where for F1 267.33 <132.67 mg/dL, F2 248.00 <147.00, mg/dL F3 217.66 <119.33 mg/dL F4 263.33 <132.67 mg/dL and F5 247.33 <114.00 mg/dL. So it can be concluded that the instant granule preparation formulation of Telang Flower extract (Clitoria ternatea L) with a dose of 450 mg/KgBB with a concentration of PVP 3.5% as a binder meets the requirements of instant granule characteristics, also has moderate antioxidant activity and has the lowest blood glucose lowering effect compared to other formulas.